2016
DOI: 10.1016/j.bjm.2016.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Microbial interactions: ecology in a molecular perspective

Abstract: The microorganism–microorganism or microorganism–host interactions are the key strategy to colonize and establish in a variety of different environments. These interactions involve all ecological aspects, including physiochemical changes, metabolite exchange, metabolite conversion, signaling, chemotaxis and genetic exchange resulting in genotype selection. In addition, the establishment in the environment depends on the species diversity, since high functional redundancy in the microbial community increases th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
145
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 278 publications
(169 citation statements)
references
References 124 publications
2
145
0
6
Order By: Relevance
“…These microorganisms are of very diverse that includes bacteria, archaea, yeast, fungi, algae, and protozoa. 1 Microorganisms can live in environment along with human and in extreme conditions such hot springs, miles deep in the ocean, inside rocks and in extreme cold temperature. 2 Although the number of microorganisms varies in different places, it has been indicated that mass of carbon from these microorganisms could be trillions of tons.…”
Section: Introductionmentioning
confidence: 99%
“…These microorganisms are of very diverse that includes bacteria, archaea, yeast, fungi, algae, and protozoa. 1 Microorganisms can live in environment along with human and in extreme conditions such hot springs, miles deep in the ocean, inside rocks and in extreme cold temperature. 2 Although the number of microorganisms varies in different places, it has been indicated that mass of carbon from these microorganisms could be trillions of tons.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the environmental establishment is dependent on species diversity as increased microbial community functional redundancy enhances the community competitive potential lowering the threshold of an invader to establish in the ambient or niche. These relationships are consequent upon co-evolution process that results in the adaptation and specialization with latitude to occupy diverse niches via the reduction of biotic and abiotic stress or in the exchange of growth factors and signaling (Braga et al, 2016). Microbial interactions take place via molecular and genetic information transfer with numerous mechanisms inculcated in the exchange, such as inter alia secondary metabolites, siderophores, quorum sensing system, biofilm formation and cellular transduction signaling.…”
Section: Metabolic Factors and Hormonesmentioning
confidence: 99%
“…Although specific microbial interactions are difficult to discern in highly complex environment, and their understanding requires the incorporation of broader influences on microbiome composition and functioning, such as those emanating from soil edaphics and plantmicrobe and microbe-microbe interactions; some microbes possess mechanisms and molecules that enable identifiable mutual interplays in complex habitats (Braga et al, 2016). Recently, members of the fungal genus Fusarium and the bacterial genus Streptomyces, notable for their capacities to produce a diverse array of antimicrobial compounds (Challis and Hopwood, 2003;Joshi, 2012), were shown to possess significant inhibitory activities against each other .…”
Section: Introductionmentioning
confidence: 99%